Positron emission tomography and pharmacokinetics of 2-[18F]-fluoroethyl choline for metabolic studies in breast cancer xenografts. (August 2014) - Kristian, Alexandr; Riss, Patrick; Qu, Hong; Milde, Mona; Schoultz, Bent W.; Engebraaten, Olav; Mælandsmo, Gunhild M.; Malinen, Eirik
Abstract Background. Breast carcinomas (BC) can have abnormal choline (Cho) metabolism. Earlier studies indicated that Cho uptake can differ between different subtypes of BC. The purpose of this study was to investigate uptake of 2-[18F]-fluoroethyl-choline ([18F]FECh) in three different patient-derived breast cancer xenografts (BCXs) using dynamic positron emission tomography (dPET). Material and methods. Nine athymic nude mice bearing bilateral MAS98.12 (basal-like), HBCx34 or MAS98.06 (both luminal B) BCXs were subjected to a 90-minute dPET scan following a bolus injection of 10 MBq of [18F]FECh. A Patlak Plot analysis and a well-established two-tissue compartment model were fitted to the uptake curves of the whole tumors, providing estimates of transfer rates between the vascular, non-metabolized and metabolized compartments. Patlak slope KP and intercept V, the rate constants k1, k2, k3, the intravascular fraction vb and MR[18F]FECh were estimated. Additionally, analyses of terminal blood samples and tumor cell suspension incubated with [18F]FECh were performed. Results. [18F]FECh uptake in all BCXs was similar to surrounding normal tissue, thus creating no image contrast. The average liver uptake was 10 times higher than the tumor uptake. The uptake in MAS98.12 was higher than in the other two BCXs during the whole course of the acquisition, and was significantly higher than in HBCx34 at 10–30 minutes after injection. No significant differences were found for k1, MR[18F]FECh and intravascular fraction vb. Patlak slope KP, k2 and k3 were significantly lower for the MAS98.12 xenograft, in line with in vitro results. KP was correlated with both MR[18F]FECh and k3. Conclusions. dPET demonstrated that different subtypes of breast cancer have different uptake of [18F]FECh. Differences in rate constants and KP were in line with in vitro uptake in cell suspensions and earlier spectroscopy and gene expression analysis.